Penguatan Karakter Kebangsaan melalui Pembelajaran Pendidikan Kewarganegaraan pada Siswa Sekolah Dasar - Reska Putri Ismail; Nur Sakinah Aries; Aina Nurdiyanti; Fidyawati Monoarfa (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2025)
This study aims to analyze the role of Civic Education learning in strengthening national character among elementary school students at SDN 4 Kwandang. The study employed a mixed-method approach through observation, interviews, questionnaires, and documentation. The results show that value-based Civic Education learning effectively improves students’ nationalism, discipline, tolerance, and sense of responsibility.